Parametric optimization of wire cut electrical discharge machining - Durairaj, M.; Ansari, A.K.S.; Gauthamkumar, M. H. (International Journal of Engineering and Technology, 2014)
Wire Electrical Discharge Machining is a manufacturing process whereby a desired shape is obtained using electrical discharges (or) by repetitive spark cycle.  Precision and intricate machining are the strengths.  Machining parameters tables provided by the machine tool manufacturers often do not meet the operator requirements. Selection of optimum machining and machining parameters combinations is needed for obtaining higher cutting efficiency and accuracy. In this present study, machining is done using Wire-Cut EDM and optimization of surface roughness is done using Taguchi’s design of experiments. Experimentation was planned as per Taguchi’s L’16 orthogonal array. Each experiment has been performed under different cutting conditions of gap voltage, pulse ON time, and pulse OFF time and Wire feed. Dielectric fluid pressure, wire speed, wire tension, resistance and cutting length are taken as fixed parameters. Inconel 800 was selected as a work material to conduct the experiments. From experimental results, the surface roughness was determined for each machining performance criteria. Signal to noise ratio was applied to measure the performance characteristics deviating from the actual value. Finally, experimental confirmation was carried out to identify the effectiveness of this proposed method.   Keywords: Optimization; Taguchi’s L-16 Orthogonal Array; Surface Roughness; S/N Ratio.